The Effect on the Fracture Healing following Femoral Neck Shortening after Osteoporotic Femoral Neck Fracture Treated with Internal Fixation: Finite Element Analysis. (5th August 2021) - Yu, Xiao; Rong, Peng-ze; Pang, Qing-jiang; Chen, Xian-jun; Shi, Lin; Wang, Cheng-hao
Abstract : Objective . To evaluate the stress status of fracture site caused by femoral neck shortening and to analyze the stress of fracture site and the implants from the finite element point of view. Methods . CT scan data of hip of a normal adult female were collected. Three-dimensional reconstruction MICs and related module function simulation was used to establish the postoperative shortening model of femoral neck fracture with Pauwels   angle > 50 °, which was treated with cannulated screws. The models were divided into four groups: normal femoral neck, shortening in 2.5 mm, shortening in 7.5 mm, and shortening in 12.5 mm. The finite element analysis software msc.nastran2012 was used, and the data of maximum stress and stress nephogram of fracture site and implants were carried out. Results . From normal femoral neck to shortening in 12.5 mm of the femoral neck, the maximum tensile stress increased gradually in the fracture site above the cannulated screws while compressive stress decreased gradually in the fracture site below the cannulated screws, and the maximum stress of the cannulated screws increased gradually with obvious stress concentration at the screw holes in the fracture site, and the peak value of stress concentration was about 179 MPa. Conclusion . The biomechanical environment of the fracture site changed by femoral neck shortening. With the increasing of femoral neck shortening, the stress of the fracture site and implants would be uneven; then, the stability of fracture site would become worse, and the possibility of implant sliding or even breakage would be increased.